Analisis Persepsi Ulama terhadap Pelaksanaan Perbankan Syariah di Kota Semarang - Fawwaz Arif Aljabar; Purbayu Budi Santosa (LPPM Institut Nasional Laa Roiba Bogor, 2021)
Ulama have an important and influential role to the Muslim societies in Indonesia. Ulama are Muslim scientists who master and well-understand of religious knowledge in Islam. At the present, Ulama also as an important figure who drives economic growth in the community in this case related to Islamic banking which conducts business activities based on sharia principles. The aim of the research is to explore the perception of Ulama towards the implementation of Islamic banking and to analyse the factors that influence the perception of Ulama in Semarang city. The method used in this research is descriptive qualitative research method. Qualitative data is collected by interviewing 3 representatives of Indonesian Muslim organization including Nahdlatul Ulama (NU), Muhammadiyah and Majelis Ulama Indonesia (MUI) in Semarang city. The data validity technique used is to use the triangulation method and the data collected are analysed by adopting the Miles and Huberman analysis model, which consists of three processes namely data reduction, data display, and conclusion drawing or verification. The results showed that the Kiai and Ulama in Semarang city which could be classified from the Nahdlatul Ulama (NU) revealed that their perceptions were limited to theories through the Qur’an and Hadits. Different from Muhammadiyah who better understand the implementation of Islamic banking because the representatives from the MUI and Muhammadiyah themselves act as Sharia Supervisory Board.